Effects of heavy barbell hip thrust vs back squat on subsequent sprint performance in rugby players - Carbone, L.; Garzón, M.; Chulvi-Medrano, I.; Bonilla, D. A.; Alonso, D. A.; Benitez-Porres, J.; Petro, J. L.; Vargas-Molina, S. (Biology of Sport, 2020)
The objective of this research was to compare the effect of Post-Activation Performance Enhancement (PAPE) exerted on the back squat (BS) versus the barbell hip thrust (HT) on the sprint performance (5- and 10-m). 17 male amateur rugby players participated in the study (age 22.14 ± 2.52 years; body mass 81.06 ± 9.6 kg; height 1.78 ± 0.05 m). All participants performed a dynamic maximum strength test (3RM) in BS and HT at maximum speed. Two randomized sessions were performed inducing PAPE using BS or HT trough three series with three repetitions at 85% 1RM eight minutes before the sprint tests. An ANOVA of repeated measurement, found no differences in the time for 5-m (F = 0.398, P = 0.537, n2p = 0.024) or 10-m (F = 2.589, P = 0.127, n2p = 0.139). There were no significant differences in the Protocol effect between HT and BS in 5-m or 10-m (F = 2.963, P = 0.104, n2p = 0.156 and F = 1.472, P = 0.243 n2p = 0.084, respectively). There were also no differences in the Time x Protocol interaction at 5-m (F = 0.001, P = 0.976, n2p < 0.001) or 10-m (F = 4.174, P = 0.058, n2p = 0.207). The effect size obtained in the results of the sprint tests was small in both exercises (ES < 0.2). None of the BS or HT exercises performed with heavy load induced a significant PAPE phenomenon on the ability to sprint in rugby players.